ANALISIS KOMPETENSI PROFESIONAL GURU IPA BERDASARKAN PENGALAMAN MENGAJAR IPA TERPADU DI SMP SEKECAMATAN SARUDU - Wijaya P, Kurniawan; Gustina, Gustina (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
This study aims to describe the professional competence of science teachers based on the experience of teaching Integrated Science in junior high schools in Sarudu. This research is a qualitative descriptive research. The respondents of this study were 6 teachers selected using purposive sampling techniques based on the teacher's teaching experience in Integrated Science learning, with details, namely 2 low experienced people, 2 moderate experienced people and 2 high experienced people. Based on the results of research on science teachers the average percentage according to teaching experience, namely teachers with low teaching experience (<6 years) obtained an average percentage of 79.13% with a high category, teachers with moderate teaching experience (6-10 years) obtained an average percentage of 84.12% with a very high category, and teachers with high teaching experience (>10 years) obtained an average percentage of 84.80% with a very high category.